Estudo da fauna de Alysiinae (Hymenoptera : Braconidae) do Parque Nacional do Itatiaia, RJ, Brasil - Cerântola, Paula de Campos Muradas (Universidade Federal de São Carlos, 2015)
The present work aims to study the fauna of Alysiinae (Hymenoptera: Braconidae) in a Dense Ombrophilous High-Montane Forest area at National Park of Itatiaia, RJ, Brazil, contributing to the taxonomic knowledge of the group as well to investigate a possible distribution pattern of these insects, related to seasonality and along an altitudinal gradient. Samples were collected with Malaise traps (Townes model, 1962), installed at four different altitudes: 987 m, 1,763 m, 2,176 m and 2,206 m. Were collected 1,082 specimens distributed in eight described genera and three possible new genera. Dinotrema Foerster, 1862, Aspilota Foerster, 1862 and Aphaereta Foerster, 1862 were the most common genera, found at the four different elevations. Ilatha Fisher, 1982 and Chaenusa Haliday, 1839 were cited for the first time in Brazil and a new species of Tanycarpa Foerster, 1862 was described. About the seasonality, the greatest abundance was observed at the hot and rainy period; concerning the altitudinal gradient, the group showed preference by highest altitudes, but to confirm these results it is necessary to add more collection sites using different collecting methods. The results of this work showed a great abundance and diversity of Alysiinae, which points the need of more studies not only at the National Park of Itatiaia, but of the whole Atlantic Forest biome, in special at the elevations.
Keywords: Ecologia; Taxonomia; Alysiinae; Itatiaia; CIENCIAS BIOLOGICAS::ECOLOGIA